PENGKAJIAN PASIEN MENGGUNAKAN FOUR SCORE COMA SCALE DI RUANG PERAWATAN INTENSIVE CARE UNIT (ICU) - Barkah Waladani; Ning Iswati (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2018)
Patients with poor conditions or decreased awareness need appropriate assessment to determine the management to be given. Awareness assessments can be done using FOUR (Full Outline of Response) scores with a range of scores from 0 to 16, consisting of eye response, motor response, brain stem reflex and respiration pattern FOUR score is used by nurses in the intensive care unit (Intensive Care Unit). ICU). The method of this study was descriptive analytical and numerator testing between oberserver prospectively to evaluate FOUR score to 100 patients in the ICU from October to December 2017. This study compared FOUR score with the GCS (Glasgow Coma Scale). Each patient was assessed using FOUR score and GCS by nurses. The average score is calculated based on the results obtained in both scoring. The results showed that the numerator test for FOUR score was very good (eye response 0.94, motor response 0.95, brain stem reflex 0.96 and respiratory pattern 1.00) and for GCS it was also very good (eye response 0.94, motoric response 0.95, verbal response 0.97). In predictive terms, GCS is better than FOUR score (characteristic curve value 0.01 difference; GCS 0.76 and FOUR score 0.75). The mortality rate of patients with FOUR scale was the lowest 0 (87%) compared with the lowest GCS score of 3 (70%). FOUR score has an excellent interpersonal and intensivisional level. In contrast to GCS, all components in FOUR score can be assessed even when the patient is installed intubation.